Vegetation growth and landscape genetics of Tillandsia lomas at their dry limits in the Atacama Desert show fine-scale response to environmental parameters - Koch, Marcus; Stock, Clara; Kleinpeter, Dorothea; Río, Camilo del; Osses, Pablo; Merklinger, Felix F.; Quandt, Dietmar; Siegmund, Alexander (Ecology and evolution, 2020)
Ecosystem dry limits have been studied in the context of species biology, fitness, and interactions with biotic and abiotic parameters, but the interactive effects of these parameters remain underexplored. Therefore, information on the putative effects of global climate change on these ecosystems is often lacking. We analyzed the interplay between fine-scale landscape genetics and biotic and abiotic factors of terrestrial Tillandsia lomas in the hyperarid Atacama Desert, characterized by a fog-dependent vegetation type almost entirely dominated by one single vascular plant species. We showed that metapopulations of Tillandsia landbeckii are genetically connected over many hundreds of square kilometers, and despite having a large potential for clonal propagation, genetic diversity is regionally and locally structured. At the landscape level, genetic diversity correlates well with fitness parameters such as growth, flowering, and vegetation density. We also observed fine-scale correlation with a 3-D landscape model indicating a positive feedback with seasonal fog occurrence and availability. The various interactions of biotic and abiotic factors resulted in regular linear banding patterns of vegetation arranged orthogonally toward the landscape slope. Ex situ growth experiments indicated that T. landbeckii grows at optimal rates in this extreme hyperarid environment, and we can extrapolate mean biomass production for this ecosystem. Synthesis. Our results suggest that the unique ecosystem of terrestrial Tillandsia lomas in the hyperarid Atacama Desert is an evolutionarily balanced and fine-scaled system. The vegetation itself is composed of long-lived and persistent modules. We developed a descriptive model of the various interacting factors, thereby also highlighting the severe threat caused by global climate change potentially associated with fog disturbance patterns along the Chilean Pacific coast.
First published: 28 October 2020
Gesehen am 19.08.2021